2016
DOI: 10.1108/jmtm-06-2014-0086
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the resiliency and sustainability of UK manufacturing companies

Abstract: Purpose -The purpose of this paper is to identify the tools, methods and models that UK manufacturing companies adopt and apply in order to achieve resiliency and economic sustainability. The results of this work can assist in developing the foundations for defining a new joint resiliency/ sustainability paradigm to assist industry. Design/methodology/approach -Through a detailed, triangulated secondary data analysis and industry survey, the authors initially identify and then analyse the key resiliency and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 30 publications
1
52
0
Order By: Relevance
“…Related to these individual methodologies, we are pleased to also see research applying multiple methods to better understand and validate findings. As in our follow-on work to explore resilience linkages (Pettit et al 2013), applying triangulation of three separate methods can provide additional support for the findings (e.g., Thomas et al 2016).…”
Section: Exposure To Risk To Riskmentioning
confidence: 80%
See 1 more Smart Citation
“…Related to these individual methodologies, we are pleased to also see research applying multiple methods to better understand and validate findings. As in our follow-on work to explore resilience linkages (Pettit et al 2013), applying triangulation of three separate methods can provide additional support for the findings (e.g., Thomas et al 2016).…”
Section: Exposure To Risk To Riskmentioning
confidence: 80%
“…), applying triangulation of three separate methods can provide additional support for the findings (e.g., Thomas et al. ).…”
Section: The Current State Of Resilience Researchmentioning
confidence: 88%
“…Cumulative growth is a better measure of long-term growth than year-over-year growth because performance growth is likely to be continuous and incremental over time. Consistent with Thomas and Byard [99], Tognazzo and Gubitta [62], and van Essen and Strike [76], we selected three years as the time period to measure firms' long-term growth. Financial volatility was measured as stock return volatility.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…While many organisations seek improvements in efficiency through "lean" supply chain solutions, to achieve resilience organisations need to be flexible and agile, for example through establishing collaborative supply chain relationships based on transparency of key information (Christopher and Peck 2008). A study by Thomas et al (2016) found that manufacturing companies that are better at applying resiliency and business sustainability models -for example, Six Sigma, quality management, lean, fit manufacture, knowledge management -are generally more economically sustainable and resilient.…”
Section: Issues Described In Existing Literaturementioning
confidence: 99%